Implementation of Regulation Sintang District Number 2th 2016 Concerning the Area Without Cigarettes - Arip Ambulan Panjaitan; Charlyna S Purba (STKIP Singkawang, 2018)
The area is free from tobacco smoke is one of the effective and inexpensive way to protect the public from the dangers of secondhand smoke. Sintang has had local regulation no smoking but in reality it can not degrade the active smoker. This study aims to determine the extent of Sintang District Regulation 2th 2016 has been implemented and the principle of the application of no smoking policy in Sintang. This study was conducted a qualitative study with approach explanatory research. Data collection was conducted in Sintang. The research subjects were 10 informants among others the Department of Health, professional organizations, community leaders, current smokers and examine documents related to the implementation of area without cigarettes (AWC). Analysis of data using content analysis. Based on the survey results showed that smokers are still accounted for 59%, still found in cigarette advertising, the lack of strict punishment for smokers, especially for employees who smoke at the office or at school. Some private companies that have implemented AWC such as Bank, while in government offices, schools and public places not yet fully be sanctions for smokers. Public opinion on the application of AWC, the majority (60%) to support the implementation of AWC, 51% of people say AWC quite effective to reduce active smokers, more than half said the informant argued that AWC should be applied at specific locations only. Opinions of respondents to smokers in public places more than half (58%) are given sanctions. Role of local government to ban new cigarette advertising and promotion can not be executed properly. Factors affecting the implementation of the AWC is dependent on the commitment of Regional Chief, Council, Department of Health and other related agencies and their empowerment. Based on this study concluded that AWC without the commitment and support of all parties is difficult for the application of AWC. In addition to the AWC to provide protection to passive smokers as well AWC can also reduce active smokers.